Antifungal potential of Lactiplantibacillus plantarum AM2 against the banana pathogen Fusarium oxysporum f. sp. cubense Tropical Race 4 - Saidi, Noor Baity; Ang, Shin Huey; Ong, Jia Xin; Wan Tajudin Shah, Wan Anati Nabilah; Abd Murad, Nur Baiti; Nur Laili (Tarbiat Modares University Press, 2024)
Fusarium wilt of bananas is a serious disease affecting banana plantations worldwide. In an effort to sustainably manage the disease, biological control is considered a promising alternative to agrochemicals that can cause detrimental effects on humans and the ecosystem. In this study, we investigated the biological control potential of the present collection of beneficial bacteria which includes Lactiplantibacillus plantarum AM2, Streptomyces morookaensis NRRL B-12429, Bacillus velezensis B4158, B. atrophaeus B363B, and B. amyloliquefaciens B942 against the causal agent of Fusarium wilt disease in banana, Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4) through a dual culture assay and a greenhouse experiment. The inhibition range in vitro was between 31.0 to 42.1%, and the highest growth inhibition of Foc TR4 was observed for L. plantarum AM2. Infected banana plantlets that received the treatment with L. plantarum AM2 also showed a significant reduction in disease severity index as low as 24% compared to treatment with other beneficial bacteria. This study showed that L. plantarum AM2 has a good antagonistic effect on Foc TR4 mycelial growth and the most potential to control Fusarium wilt disease in bananas.